Maltrato físico, psicológico y su incidencia en el aprendizaje de un niño de 11 años de la ciudadela Las Américas del cantón Milagro provincia del Guayas - Rocafuerte Lecaro, Susana Jahaira (2018)
Physical and psychological abuse is a problem that exists in several homes in the Milagro canton, many parents for wanting to discipline their children mistreat them, ignoring that physical and / or psychological abuse is not a discipline, ignoring the damage they can cause. The child suffering from physical and / or psychological abuse will generate in the depressive symptomatology. The depression caused in the child can influence the academic performance as it is in this case of an 11-year-old boy who, when physically and psychologically abused, has a low academic performance. In the present clinical case, a physically and psychologically abused child with depressive symptomatology was described, which was carried out in the Las Americas del Canton Milagro citadel, which had effects on a child's optimal academic performance, to know which were the factors that influenced the maintenance and what was its main trigger. Subsequently, they were analyzed and a Cognitive-Behavioral cut-out scheme was shown for their psychological treatment with the patient. Proposals are also recommended at the individual and collective level to prevent this problem